1993
DOI: 10.1177/0115426593008004177
|View full text |Cite
|
Sign up to set email alerts
|

Basic Concepts of Immunology and Its Application to Clinical Nutrition

Abstract: In recent years, evidence has accumulated on the effects of nutrients on metabolic processes. The role of specific nutrients in modulating immune function has received much attention because of the significant role of the immune system in a variety of disease states. The immune system depends on the complex interactions of its various parts. In response to an "antigen" or foreign substance that penetrates the external protective barriers of the human body, nonspecific (phagocytes, complement) defense mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…Through the collection of serum and urine samples within 24 hours of hospitalization, we measured serum and urine selenium levels and systemic inflammatory indicators, such as CRP, procalcitonin and total WBC counts, and their fractions. Of the differential counts, lymphocyte counts were served as one of the indicators of nutritional status along with albumin levels (12)(13)(14). In accordance with a previously conducted study in patients staying at surgical ICU, it was confirmed that micronutrients including selenium reduced at the time of hospitalization were recovered to the normal range within 1 week (15).…”
Section: Outcome Measures and Assessmentsupporting
confidence: 60%
See 1 more Smart Citation
“…Through the collection of serum and urine samples within 24 hours of hospitalization, we measured serum and urine selenium levels and systemic inflammatory indicators, such as CRP, procalcitonin and total WBC counts, and their fractions. Of the differential counts, lymphocyte counts were served as one of the indicators of nutritional status along with albumin levels (12)(13)(14). In accordance with a previously conducted study in patients staying at surgical ICU, it was confirmed that micronutrients including selenium reduced at the time of hospitalization were recovered to the normal range within 1 week (15).…”
Section: Outcome Measures and Assessmentsupporting
confidence: 60%
“…Serum albumin is an indicator of protein reserves (14,24). In addition, total lymphocyte counts are used as an indicator of immune defenses due to malnutrition (12,13). Thus, they are considered as a useful indicator of nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…The Controlling Nutritional Status (CONUT) method is an automated malnutrition screening and alert tool for patients hospitalized with acute diseases [ 26 ]. Moreover, serum albumin, TC, and total lymphocyte count were used as indicators of storage and availability of protein stores [ 27 ], energy reserves [ 28 ], and impaired immune defense, respectively, and are closely linked to malnutrition [ 29 ]. The scoring criteria (maximum of 12 points) were as follows: 0–4 points, low risk; 5–8 points, moderate risk; and 9–12 points, high risk.…”
Section: Methodsmentioning
confidence: 99%
“…The specimen collection and processing procedures have been described elsewhere [36]. Levels of serum albumin may indicate protein reserve levels [37,38], and low total lymphocyte count may be associated with low immune function caused by undernutrition [39,40,41]. Participants in the analytic sample were classified by PNI quintiles, with participants in quintile 1 (lowest PNI scores) indicating a relatively higher risk of malnutrition whereas those in quintile 5 (highest PNI scores) indicating a relatively lower risk of malnutrition.…”
Section: Methodsmentioning
confidence: 99%